2011
DOI: 10.1007/s11605-010-1292-x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Mutations and Prognostic Factors Analysis in Extragastrointestinal Stromal Tumor of a Chinese Three-Center Study

Abstract: The pattern of c-kit and PDGFR-α mutation in EGISTs was essentially similar to that in GISTs. From the molecular genetics aspect, EGISTs may be a special subtype of GISTs. The results also show that the combination of mitotic counts and Ki-67 LI may be useful for predicting the prognosis of EGISTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 14 publications
5
19
0
Order By: Relevance
“…In contrast with our study cohort, male (56.4% vs 43.6%) cases were predominant, and the mean age of tumor occurrence was 58 years old. We hypothesize that this may be related to population ethnicity, as in the analysis of previous study, 23 among the eight studies investigated, only one 24 was from China, and in that study, male cases were also predominant (60% vs 40%) at a mean age of 60 years old, resonating to that of our findings. However, more studies are required to validate this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast with our study cohort, male (56.4% vs 43.6%) cases were predominant, and the mean age of tumor occurrence was 58 years old. We hypothesize that this may be related to population ethnicity, as in the analysis of previous study, 23 among the eight studies investigated, only one 24 was from China, and in that study, male cases were also predominant (60% vs 40%) at a mean age of 60 years old, resonating to that of our findings. However, more studies are required to validate this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…The findings of previously published studies on extragastrointestinal stromal tumors (EGIST) have led authors to believe that these tumors are histologically and immunohistochemically similar tumors, with features that are also similar to those found in gastrointestinal stromal tumors (GIST), including the expression of c-KIT and PDGFR- α gene mutations [ 4 , 14 , 15 ] (Song Zheng, Huang, Tao, & Pan, 2011). The similar findings from previous studies have supported the assumption that GIST and EGIST arise from similar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al demonstrated that the c-kit and PDGFRA mutation in EGISTs was similar to that of GISTs. Therefore, from a molecular genetics perspective, EGISTs may be a unique subtype of GISTs (3). …”
Section: Discussionmentioning
confidence: 99%
“…A tumor size >10 cm, mitotic activity >2 per 50 high-power fields, tumor necrosis, marked nuclear atypia, >10% Ki-67 protein expression and epithelioid-/mixed cell-type, have acted as significant predictors of survival (2,3). Survival analysis indicated that mitotic count and Ki-67 protein expression levels were significant predictors of disease-specific survival; however, tumor size, primary location, c-kit and PDGFRA gene mutations were not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation